Numerical Modelling of Triangular Corrugated-core Sandwich Panel subjected to Impact Loading - M. R. M., Rejab; S. H. S. M., Fadzullah; K. A., Kamarudin; F., Mat (UTEM Press, 2015)
In this paper, lightweight aluminium AL2024-O sandwich panels were tested using drop-weight impact tower with lateral impactor to evaluate impact responses and to identify the associated failure mechanisms under various impact loading conditions. The simulations of impact responses of triangular corrugated-core sandwich panels were presented, which were validated against the corresponding experimental data. The triangular corrugated-core sandwich panel configurations were studied by using commercial finite element (FE) code, Abaqus/Explicit. The FE code is used to develop numerical models by using plasticity with strain hardening, and ductile damage criteria, etc., to cover the most representative cases. A good agreement was obtained, which indicates the finite element models developed are capable of predicting the dynamic behaviour of the triangular corrugated-core sandwich panels subjected to uniform lateral impact.